Knowledge of The Physical Health Conditions Associated with Excessive Screen-Time Leisure Activities Among Undergraduate Students of University of Nigeria, Nsukka - Abbah, Oliver I.; Nguungwan, Seer-Uke Eunice; Okeke, Adaustin Ifeoma; Echezona, Bridget I.; Ugwu, Stella Uzoamaka; Omeje, Juliana Nkasiobi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The study assessed knowledge of physical health conditions associated with excessive screen time leisure activities among undergraduate students in University of Nigeria, Nsukka. The descriptive research design was adopted for the study. The population for the study consisted of 19,973 undergraduate students of University of Nigeria, Nsukka campus. A sample size of 392 students obtained using the Taro Yamane formula for a finite population. The instrument for data collection was designed by the researchers. It was validated by three experts from the Department of Human Kinetics and Health Education, University of Nigeria, Nsukka, and has a reliability coefficient of 0.73. Frequency and percentages were used to answer the research questions, while chi square statistics was used to test the hypotheses at 0.05 level of significance. Level of knowledge was determined using the Ashur (1997) scale for describing level of knowledge. Results indicated that undergraduate students of University of Nigeria, Nsukka, possess low (49%) level of knowledge of active lifestyle problems associated with excessive screen time leisure activities. The study also revealed that undergraduate students of University of Nigeria, Nsukka possess very high (80%) level of knowledge of vision related problems and high (68%) level of knowledge of musculoskeletal disorders associated with excessive screen time leisure activities. There was no significant difference in level of knowledge of physical health conditions associated with excessive screen time leisure activities among undergraduate students based on gender (p > 0.05) and year of study (p > 0.05). It was recommended that the authority of the University of Nigeria, Nsukka should organize public health awareness programme where students should be educated on the health implications of excessive screen time use.